The IGF2 mRNA binding protein p62/IGF2BP2-2 induces fatty acid elongation as a critical feature of steatosis - Laggai, Stephan (The American Society for Biochemistry and Molecular Biology, 2014)
Liver-specific overexpression of the insulin-like growth factor 2 (IGF2) mRNA binding protein p62/IGF2BP2-2 induces a fatty liver, which highly expresses IGF2. Because IGF2 expression is elevated in patients with steatohepatitis, the aim of our study was to elucidate the role and interconnection of p62 and IGF2 in lipid metabolism. Expression of p62 and IGF2 highly correlated in human liver disease. p62 induced an elevated ratio of C18:C16 and increased fatty acid elongase 6 (ELOVL6) protein, the enzyme catalyzing the elongation of C16 to C18 fatty acids and promoting nonalcoholic steatohepatitis in mice and humans. The p62 overexpression induced the activation of the ELOVL6 transcriptional activator sterol regulatory element binding transcription factor 1 (SREBF1). Recombinant IGF2 induced the nuclear translocation of SREBF1 and a neutralizing IGF2 antibody reduced ELOVL6 and mature SREBF1 protein levels. Concordantly, p62 and IGF2 correlated with ELOVL6 in human livers. Decreased palmitoyl-CoA levels, as found in p62 transgenic livers, can explain the lipogenic action of ELOVL6. Accordingly, p62 represents an inducer of hepatic C18 fatty acid production via a SREBF1-dependent induction of ELOVL6. These findings underline the detrimental role of p62 in liver disease.